2007
DOI: 10.1016/j.jtcvs.2007.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and safety of intravenously administered citrulline in children undergoing congenital heart surgery: Potential therapy for postoperative pulmonary hypertension

Abstract: In this first report of the use of intravenous citrulline in humans, we found citrulline to be both safe and well tolerated in infants and young children undergoing congenital cardiac surgery. Because of the rapid clearance, the optimal dosing regimen was identified as an initial bolus of 150 mg/kg given at the initiation of cardiopulmonary bypass, followed 4 hours later by a postoperative infusion of 9 mg/(kg.h) continued up to 48 hours. Using this regimen, plasma arginine, citrulline, and nitric oxide metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
51
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 11 publications
2
51
0
Order By: Relevance
“…Moreover most important, the urea cycle and the nitric oxide cycle are linked via ASS1 and ASL. Previous studies 5,6 have shown that a quantitative change in urea cycle enzyme expression and function can affect nitric oxide production by limiting substrate availability. Therefore, the abnormalities within the urea cycle result in urea cycle disorder and affect other physiological systems.…”
mentioning
confidence: 99%
“…Moreover most important, the urea cycle and the nitric oxide cycle are linked via ASS1 and ASL. Previous studies 5,6 have shown that a quantitative change in urea cycle enzyme expression and function can affect nitric oxide production by limiting substrate availability. Therefore, the abnormalities within the urea cycle result in urea cycle disorder and affect other physiological systems.…”
mentioning
confidence: 99%
“…Together, these findings suggest that superoxide production and not NO production is the predominant role for NOS-3 in the pathogenesis of VILI in this model, thus providing in vivo evidence for uncoupling of NOS as a mechanism for oxidative stress in VILI. In support of this, treatment of wild-type mice with the NOS-3 cofactor BH 4 and the antioxidant ascorbic acid led to a reduction in VILI, presumably via enhanced coupling of NOS-3. The major limitation of this study was the use of a supraphysiological tidal volume to induce VILI, limiting the potential clinical relevance of the findings.…”
mentioning
confidence: 80%
“…A second factor that can lead to uncoupling of NOS is insufficiency of the NOS cofactor tetrahydrobiopterin (BH 4 ), which is normally bound to the oxygenase domain (22). Factors that can lead to reductions in BH 4 include oxidative stress (8) and ischemia reperfusion (22). Reactive oxygen species can also react with NO to form peroxynitrite.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical studies, oral L-citrulline increased both plasma citrulline and arginine levels in highrisk children undergoing cardiopulmonary bypass [45]. Intravenous L-citrulline has been shown to be safe and well tolerated in children undergoing cardiopulmonary bypass [46], and clinical trials are underway. …”
mentioning
confidence: 99%